GEOGRAPHICAL POSITION AND NATURAL RESOURCES OF THE GREAT BRITAIN - Zokirjonov Ro‘zimuhammad,; Abdurakhmanov Turakhon Saydullayevich, (TADQIQOTLAR, 2025)
Annotation This scientific work is devoted to the study of the geographical position and natural resources of Great Britain. Located in the northwestern part of Europe, Great Britain has a strategic maritime position near major sea routes, which has significantly influenced its historical, economic, and political development. The country's varied topography—including mountains and lowlands—and its temperate maritime climate have provided favorable conditions for the development of agriculture and industry.